UPAYA PENDIDIKAN MADRASAH DINIYAH DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATERI FIQIH DI MADRASAH DINIYAH MIFTAHUL ULUM PRUTEN NGEMBAL PASURUAN - M Jamhuri (Universitas Yudharta Pasuruan, 2017)
Madrsah Diniyah is an educational institution and Islamic teaching that serves to carry out the main task as a Muslim, to realize the classical religion education in accordance with the demands of the classical students so that children get more Islamic education which in turn will be Can mengamalkannya that no other just for their salvation either in the world or in the hereafter.This research problem originally started from three subjects: (1) learning achievement of fiqih subjects: (2) Madrasah effort in improving learning achievement fiqih. (3) supporting and inhibiting factors that influence Madrasah Diniyah in improving learning achievement on fiqih material. The purpose of this research is to find out what efforts are done by Madrasah in improving student learning.To reveal from three factors above, researcher use approach type of qualitative research. Researcher take object in Madrasah Diniyah Miftahul Ulum Pruten Ngembal Tutur Pasuruan, while to collect data of researcher use three method that is observation (Observation), interview (Interview), and documentation with respondent of teacher of subject of fiqih subject which is two people, and researcher take sample Which numbered 23 from 123 students to the data of student achievement on fiqih subjects covering three aspects, namely: cognitive (knowledge), effective (attitude), psychomotor (habituation).From the above description, the researcher gives suggestions so that a teacher can improve the learning achievement in fiqih material by improving the teaching and learning activities, increasing the allocation of time, increasing the student's discipline in the classroom and improving the quality of the teacher of fiqih study. This is done so that the learning process takes place properly.